Higher serum undercarboxylated osteocalcin and other bone turnover markers are associated with reduced diabetes risk and lower estradiol concentrations in older men - Yeap, B.; Alfonso, Helman; Chubb, S.; Gauci, R.; Byrnes, E.; Beilby, J.; Ebeling, P.; Handelsman, D.; Allan, C.; Grossmann, M.; Norman, P.; Flicker, L. (2015)
Context: In mice, undercarboxylated osteocalcin (ucOC) modulates insulin secretion and sensitivity and increases testosterone (T) secretion from Leydig cells, but human data are lacking. We hypothesized that ucOC is associated with diabetes risk and modulates sex hormone concentrations in older men, distinct from other bone turnover markers. Participants: Participants were community-dwelling men aged 70 to 89 years resident in Perth, Western Australia. Main Outcome Measures: Serum total osteocalcin (TOC), N-terminal propeptide of type I collagen (P1NP), and collagen type I C-terminal cross-linked telopeptide (CTX) were measured by immunoassay, and ucOC by hydroxyapatite binding. Plasma total T, DHT, and estradiol (E2) were assayed by mass spectrometry.Results: Excluding men with osteoporosis or conditions affecting sex hormones or on bisphosphonates, glucocorticoids, or warfarin, 2966 men were included. In multivariate analyses, higher ucOC was associated with reduced diabetes risk (odds ratio [OR] per 1 SD increase = 0.55, P < .001). Similar results were seen for TOC (OR = 0.60, P < .001), P1NP (OR = 0.64, P < .001), and CTX (OR = 0.60, P < .001) but not ucOC/TOC. When all 4 markers were included in the fully adjusted model, higher ucOC (OR = 0.56, P < .001) and CTX (OR = 0.76, P = .008) remained associated with reduced diabetes risk. E2 was inversely associated with ucOC (coefficient −0.04, P = .031), TOC (−0.05, P = .001) and CTX (−0.04, P = .016); and positively with ucOC/TOC (0.05, P = .002). DHT was inversely associated with ucOC/TOC (−0.04, P = .040). T was not associated with bone turnover. Conclusions: Higher bone remodeling rates are associated with reduced diabetes risk in older men. Higher ucOC is both a marker of bone remodeling and an independent predictor of reduced diabetes risk. E2 is inversely associated with bone turnover markers. We found no evidence ucOC modulates circulating T in older men.